Computer science - J Glenn Brookshear (Addison-Wesley, 1997)
The book provides accurate and balanced coverage of a variety of topics, providing an overview to the discipline of computer science. It also includes a larger emphasis on the object-oriented paradigm and networking, including coverage of the World Wide Web and the JavaTM Programming Language; offers end-of-chapter "Questions of Ethics" in addition to the ethics discussions throughout the book; contains new sections on digital circuitry, the client/server model, data compression, and digital representation of graphics; provides a complete teaching package, including a new C++ lab manual, C and Pascal lab manuals, and a World Wide Web site